Improvement in All‐Cause Mortality With Blood Pressure Control in a Group of US Veterans With Drug‐Resistant Hypertension. Issue 1 (6th October 2015) - Fatemi, Omid; Goa, Cristobal; Faselis, Charles; Kokkinos, Peter; Papademetriou, Vasilios
Abstract : The current definition of drug‐resistant hypertension includes patients with uncontrolled (URH) (taking ≥3 antihypertensive medications) and controlled hypertension (CRH; blood pressure [BP] ≤140/90 mm Hg) (taking ≥4 medications). The authors hypothesized that all‐cause mortality is reduced when URH is controlled. Qualified patients followed at the Washington DC VA Medical Center were included. BPs were averaged for each year of follow‐up. In 2006, among 2906 patients who met the criteria for drug‐resistant hypertension, 628 had URH. During follow‐up, 234 patients were controlled (group 1) and 394 patients remained uncontrolled (group 2). The mortality rate among patients with URH was 28% (110 of 394) and among patients with CRH was 13% (30 of 234), a 54% reduction ( P <.01). Multivariate analysis identified independent predictors of mortality as uncontrolled HTN (hazard ratio, 2.5; 95% confidence interval, 1.67–3.75; P <.01), age (hazard ratio, 1.03; 95% confidence interval, 1.01–1.04; P <.01), and diabetes (hazard ratio, 1.46; 95% confidence interval, 1.04–2.05; P <.027). The authors conclude that controlling drug‐resistant hypertension markedly reduces all‐cause mortality.